Notoginsenoside R1 protects hypoxia-reoxygenation deprivation-induced injury by upregulation of miR-132 in H9c2 cells. (December 2021) - Jin, Z; Gan, C; Luo, G; Hu, G; Yang, X; Qian, Z; Yao, S
Background: Myocardial ischemia/reperfusion injury (IRI) is a common perioperative complication of heart and great vessels surgery, aggravating the original myocardial damage and seriously affecting the postoperative recovery of cardiac function. The aim of this study was to reveal the functional effects and potential mechanisms of notoginsenoside R1 (NG-R1) in myocardial cells injured by hypoxia-reoxygenation (H/R). Methods: The rat cardiomyocyte line H9c2 was subjected to H/R with or without NG-R1 treatment. The levels of miR-132 and HBEGF in the cell were altered by microRNA or short-hairpin RNA transfection. Cell viability, apoptosis, lactate dehydrogenase (LDH) and malondialdehyde (MDA) were monitored. Dual luciferin was used to detect the relationship between miR-132 and HBEGF. Results: NG-R1( 20 μM) had no impact on H9c2 cells, but cell viability was significantly reduced at 80 μM. NG-R1 (20 μM) protected H9c2 cells against H/R-induced cell damage, accompanied by increased cell viability, reduced cell apoptosis, and downregulation of LDH and MDA. Furthermore, the level of miR-132 was decreased in response to H/R exposure but then increased after NG-R1 treatment. When miR-132 was overexpressed, H/R-induced cell damage could be recovered. Downregulation of miR-132 limited the protective effect of NG-R1 on H/R damage. We also found that HBEGF was a direct target of miR-132. The expression of HBEGF was increased upon H/R damage, and this increase was reversed after NG-R1 treatment. Conclusions: This study demonstrated that NG-R1 markedly protected H9c2 cells against H/R-induced damage via upregulation of miR-132 and downregulation of its target protein HBEGF.